MORPHOLOGICAL ANALYSIS ON THE WORD IN THE E-COMMERENCE TERM - Trimastuti, Wahyu; Christinawati, Santy (Journal of English Language Teaching and Literature, 2018)
The purpose of the research is to discuss the form of morphology on the words in the e-commerce terms. It describes the types of word formation and explain the meaning of the terms. In analyzing the data the writer uses morphology analysis. The research is qualitative research. The data are taken from e-commerce terms. The writer uses document and observation method to collect the data. The writer analyses the words based on the elements of words. In this research showed that the word formation categories that found in the e-commerce terms are derivation word, compounding word, and phrase. Those terms have complexity in the process of its formation and have specific meaning. Therefore, it necessary to be explained more detailed to avoid misunderstanding in communication.